Hardware Implementation of a Modified Delay-Coordinate Mapping-Based QRS Complex Detection Algorithm. (5th April 2007) - Cvikl Cvikl, Matej Matej; Jager Jager, Franc Franc; Zemva Zemva, Andrej Andrej
Abstract : We present a modified delay-coordinate mapping-based QRS complex detection algorithm, suitable for hardware implementation. In the original algorithm, the phase-space portrait of an electrocardiogram signal is reconstructed in a two-dimensional plane using the method of delays. Geometrical properties of the obtained phase-space portrait are exploited for QRS complex detection. In our solution, a bandpass filter is used for ECG signal prefiltering and an improved method for detection threshold-level calculation is utilized. We developed the algorithm on the MIT-BIH Arrhythmia Database (sensitivity of 99.82% and positive predictivity of 99.82% ) and tested it on the long-term ST database (sensitivity of 99.72% and positive predictivity of 99.37% ). Our algorithm outperforms several well-known QRS complex detection algorithms, including the original algorithm.